THE EFFECT OF READING METHODS ON INCREASING THE READING ABILITY OF PRIMARY STUDENTS - Rasmitadila; Rachmadtullah, Reza; Samsudin, Achmad; Aliyyah, Rusi Rusmiati; Humaira, Megan Asri; Syaodih, Ernawulan (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to analyze the reading ability of students who learn through the reading method of structural analysis synthesis (SAS) with the reading method of pictures and syllables (Gasuka). The research was conducted using an experimental method with Pretest-Posttest Control Group Design. The technique of collecting data used the oral test. The data analysis technique was conducted through a normality test, homogeneity test, and two- t-test. The results showed that there were differences in students’ reading ability between groups taught using SAS reading method with Gasuka reading method. Other results also show that the group using the SAS reading method has an average value of N-gain of 0.55, while in the group using the Gasuka reading method has an average value of N-gain of 0.59. So, it can be concluded that the SAS reading method and Gasuka reading method can improve students’ reading ability.